101k views
21 votes
Somebody please help me with this !!!

Somebody please help me with this !!!-example-1
User Taile
by
6.9k points

1 Answer

3 votes

Explanation:

Case 1 :


3x + 2y = 6 \\ 4x + y = 2 \\ 3x = 6 - 2y \\ x = (6 - 2y)/(3) = \\ x = 2 - (2y)/(3) \\ 4(2 - (2y)/(3) ) + y = 2 \\ 8 - (8y)/(3) + y = 2 \\ - 1.67y = - 6 \\


y = 3.59 \\ x = 2 - (2y)/(3) \\x = 2 - (2 * 3.59)/(3) \\ \\ x = - 0.39

Case 2 :


3x + 2y = 6 \\ 4x - y = 2 \\ x = 2 - (2y)/(3) \\ 4(2 - (2y)/(3) ) - y = 2 \\ 8 - (8y)/(3) - y = 2 \\ - 3.67y= - 6 \\ y = 1.63


x = 2 - (2y)/(3) \\ x = 2 - (2 * 1.63)/(3) \\ x = 2 - 1.087 \\ x = 0.913

User Jagttt
by
6.5k points